Panniculitis in a 3‐year‐old child with Fanconi anemia‐associated bone marrow hypoplasia heralds transformation to acute myeloid leukemia. Issue 5 (18th July 2019) - Webber, Lucy; Cummins, Michelle; Mann, Rebecca; Shaw, Lindsay; Ghinai, Rosanna; Mahon, Caroline
Abstract: Fanconi anemia is a rare, autosomal recessive genomic instability disorder characterized by congenital limb anomalies, panmyelopathy and a high risk of malignancy, principally acute myeloid leukemia. Hematologic malignancy presenting with acute febrile neutrophilic dermatosis (Sweet syndrome), both deep and superficial forms, is well described in Fanconi anemia patients but is a rare phenomenon in otherwise healthy children. We present a case of panniculitis (presumptive subcutaneous Sweet syndrome) heralding transformation to acute myeloid leukemia in a 3‐year‐old boy with a severe Fanconi anemia phenotype.